Synergistic Effects of E2MATE and Norethindrone Acetate on Steroid Sulfatase Inhibition: A Randomized Phase I Proof-of-Principle Clinical Study in Women of Reproductive Age. (October 2014) - Pohl, Oliver; Bestel, Elke; Gotteland, Jean-Pierre
The combination of a progestin such as norethindrone acetate (NETA) reducing the ovarian estrogen production with a steroid sulfatase (STS) inhibitor (STS-I) decreasing the local estrogen production could result in a new treatment option for endometriosis. The study reported was a randomized, double-blind, and placebo-controlled study to investigate the pharmacodynamics, pharmacokinetics, and safety of the STS-I PGL2001 (E2MATE) and NETA. A total of 24 healthy women of reproductive age were treated with weekly doses of PGL2001 or daily doses of NETA or a combination of both compounds for 4 weeks. Four weeks of treatment with PGL2001 or PGL2001 + NETA reduced the STS activity in the endometrium by 91% (±3%) and 96% (±4%), respectively, and comparable values were observed 1 month after the treatment was stopped. The combined treatment of PGL2001 + NETA led to significantly higher STS inhibition at both times ( P < .01 and P < .05, respectively). This study showed that administration of PGL2001 alone at 4 mg/week or combined with NETA to healthy women of reproductive age led to STS inhibition and changes in functional STS biomarkers in the endometrium, resulting in synergistic effects of PGL2001 and NETA on STS activity.